Conducting social network analysis with animal telemetry data: Applications and methods using spatsoc. Issue 8 (28th June 2019) - Robitaille, Alec L.; Webber, Quinn M. R.; Vander Wal, Eric
Abstract: We present spatsoc, an r package for conducting social network analysis with animal telemetry data. Animal social network analysis is a method for measuring relationships between individuals to describe social structure. Proximity‐based social networks are generated from animal telemetry data by grouping relocations temporally and spatially, using thresholds that are informed by the characteristics of the species and study system. spatsoc fills a gap in r packages by providing flexible functions, explicitly for animal telemetry data, to generate edge lists and gambit‐of‐the‐group data, perform data‐stream randomization, and generate group by individual matrices. The implications of spatsoc are that current users of animal telemetry or otherwise georeferenced data for movement or spatial analyses will have access to efficient and intuitive functions to generate social networks.